Improved DSSC performance with acidic extract of Euphorbia milii red flower, the effect of pH variation and DFT analysis of phytoconstituents - Nikhil Srivastav; Kalpajyoti Dihingia; Himanshu Patel; Yoganand Singh; Ananya Rai; Biswajit Maiti; Pankaj Srivastava (Next Materials)
Dye-sensitized solar cells (DSSCs) have garnered significant attention in recent years, surpassing traditional solar cells in terms of cost-effectiveness, ease of fabrication, and operation in low-light conditions. However, the synthesis of dyes, crucial for DSSCs, is often complex and involves hazardous or trace metals, prompting the exploration of natural dyes as an alternative. Euphorbia milii (E.milii) plants have already been recognized for their medicinal uses and application as a natural acid-base indicator. In this study, an acid-mediated extract of E. milii red flowers was prepared and effect of post-extraction pH variation was studied. The modified extracts were subsequently utilized as a sensitizer in TiO2 based DSSCs. Phytochemical studies were carried out to ensure the presence of constituents in the obtained extract. The UV-Vis spectra indicated a widening of the absorption range with variation in the pH. The Cyclic Voltammogram showed the redox nature of the acidic extract obtained at different pH. The UV-Vis and FTIR analysis revealed potential functional groups belonging to phytoconstituents that interact with the TiO2 surface effectively. PL and TRPL studies were also carried out to analyse the excited state dynamics. DFT (Density Functional Theory) and TD-DFT (Time-dependent DFT) were carried out using B3LYP and CAM-B3LYP functional respectively at 6–311++G(d, p) basis set and solvent effect was studied in ethanol over SMD model to validate the experimental environment and corresponding results. The HOMO-LUMO position and the band-gap were determined for the various phytoconstituents. Further, the ΔGinj, ΔGreg and the LHE (light harvesting efficiency) values were estimated. These analyses led to the viability of the extract as a sensitizer-dye. The photovoltaic parameters i.e., Jsc, Voc, photo conversion efficiency (η), and fill factor (FF) were investigated for the fabricated cell. Additionally, stability and electrochemical impedance spectroscopy (EIS) studies for the charge transfer characteristics, were also performed. Among all pH levels, relatively high absorption intensity, photocurrent (Jsc=0.7mAcm−2) and electron lifetime (τe=7ms) were recorded for pH 3.1 extract-based cell.